Caracterización morfológica de los órganos vegetativos y reproductivos de Cinchona officinalis L., provenientes de dos relictos boscosos en la provincia de Loja - Correa Torres, Gabriela Dayanara (2021)
Cinchona officinalis L., is a species that is often confused with other species of the genus Cinchona such as: C. capuli L. Andersson, C. lancifolia Mutis and C. macrocalyx Pav. ex DC., because they share similar morphology, habitat and altitude range. This research was developed with the purpose of providing information on the morphological characteristics of the vegetative and reproductive organs of the species, through the use of qualitative-quantitative descriptors. This study was carried out in the sectors of Selva Alegre and Uritusinga, in the province of Loja. Based on the identified characteristics, a descriptive statistical analysis was carried out, which allowed observing the morphological variability of the species in the two study areas. The results revealed that the trees of C. officinalis L., reached heights between 3 to 9 m, with opposite and decused phyllotaxia; the leaf presented an oval shape, 7.3 to 16.9 cm long, with an entire edge, and a penninervial rib; In the variables such as width and leaf area of the leaf, dissimilarity of values was evidenced between the two sites, with Selva Alegre presenting the highest value in the width of the leaf of 4.33 cm. The flower presented an average length of 1.37 cm, small, actinomorphic, tubular. The Selva Alegre flowers presented the highest percentage in the corolla area of 0.64 cm, with an average length of the stamens of 1.06 cm; while Uritusinga reached the highest value in the length of the style of 1.04 cm. The fruit presented an oblong or elliptical shape, dark red, 2.48 cm long; the highest number of seeds per fruit was evidenced in Uritusinga, with the presence of 39 seeds / fruit, and with an average length of 5.73 mm. Therefore, it could be concluded that the two sectors did not show great difference in relation to the qualitative characteristics of the leaf, fruit and seeds, however, slight dissimilarity was observed in the flowers of the two sites, as well as in the variables quantitative values evaluated, where a difference in values was evidenced. Based on this information, it is expected to strengthen the bases of the theory for subsequent investigations that prioritize the management, taxonomic identification and genetic improvement of the species. Key words: Morphological characterization, Cinchona officinalis L., vegetative organs, reproductive organs.